Review of Community Service Activities Themed Capital for Micro, Small and Medium Enterprises (UMKM): Ulasan Kegiatan Pengabdian Masyarakat Bertemakan Pemodalan Usaha Mikro Kecil dan Menengah (UMKM) - Dharmayanti Pri Handini; Endah Puspitosarie; Alfiana; Syamsul Bahri (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The capital aspect is one of the problems in the micro, small and medium enterprise (MSME) sector. This capital problem has become a theme or topic for community service activities in higher education circles. A review can be carried out as a form of study that is useful for similar activities. The aim of writing this article is to obtain the results of a review of community service activities with the theme of MSME capital. The review was carried out by searching publications for the last 5 years. Reviews are carried out in categories of number of activities per year, activity themes and partners/target groups. The results of the review show that the number of activities tends to increase every year. Information and access to capital are the main themes of the activity with MSME groups as partners or activity targets.